If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 7(-12 + x) = -38 4 + (-12 * 7 + x * 7) = -38 4 + (-84 + 7x) = -38 Combine like terms: 4 + -84 = -80 -80 + 7x = -38 Solving -80 + 7x = -38 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '80' to each side of the equation. -80 + 80 + 7x = -38 + 80 Combine like terms: -80 + 80 = 0 0 + 7x = -38 + 80 7x = -38 + 80 Combine like terms: -38 + 80 = 42 7x = 42 Divide each side by '7'. x = 6 Simplifying x = 6
| 24+14x=x | | 3y+z=am | | [6x-4]=-52 | | 4x-10=6x+12 | | 14x+24=x | | 6x-4=-52 | | 6x-7=5x+6 | | 8x-1=8x-x | | 6x+8x=x | | -9=x+12 | | 3x+5x-15=37 | | 7x+1=7x-x | | a(b-c)=d | | x+108=100 | | 8+4d=36 | | 18+108=126 | | 8+4d=37 | | z=6*3.14xy | | 2-11x=122+x | | 20+3n=-4 | | -9x-4=23 | | 13-7x=58-28x | | 3(z-5)+6z-1= | | 2x+2x-5=19 | | 10x-130=1 | | 6k-(3k-6)= | | 8-3y=-13 | | 4x+5=41 | | 2+5x=26+5x | | (n-9)*9=27 | | 3(5x-1)=60 | | 2x+7y=24 |